The Peril of Covid-19 in Health and Education : Effectiveness of Basic Electrical Wiring System Online Teaching (Cuestiones de Fisioterapia, 2025)
In recent years, online teaching has emerged as a prominent educational method, especially in response to global events such as Covid-19 pandemic that necessitated changes in traditional learning environments. Despite its challenges, the utilization of online teaching has shown remarkable benefits, particularly in student performance. Based on the pre-test results reflected that there are 11 student respondents, First Year Bachelor of Technical-Vocational Teacher Education (BTVTED) students of Mindoro State University taking the basic electrical wiring system before shifting to online mode achieved a “Fair “performance, and 9 of them gained a “Satisfactory” status. On the other hand, at least one of them out of 20 individuals obtained a “Poor” performance. The overall mean for the Pre-test of the study was 11.71 treated as “Poor” performance. The analysis of post-test outcomes revealed a significant level of achievement among the student respondents. Out of the total participants, 18 students were classified as “Outstanding,” reflecting a high level of understanding and engagement with the course material. Additionally, 2 students earned a rating of “Very Satisfactory,” while only one student received a “Fair” performance designation. These results culminated in an overall mean score of 27.52, which is categorized as “Outstanding.” This data suggests that the transition to online teaching has not only maintained educational standards but has also fostered an environment in which a majority of students thrive academically. The interactive nature of online platforms fosters greater engagement and collaboration among peers, further enhancing the educational experience.